Penggunaan Film Sejarah dalam Pembelajaran Menulis Teks Drama pada Siswa Kelas XI.2 SMA Taruna Mandara - Ni Putu Dina Aprilia Putri; Ade Asih Susiari Tantri; I Nyoman Yasa (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the planning of the use of historical films in learning to write drama texts for Class XI.2 students at SMA Taruna Mandara, describe the implementation of using historical films in learning to write drama texts for Class XI.2 students at SMA Taruna Mandara, describe the students’ ability to write drama texts using historical films, and describe the students’ responses to the use of historical films in learning to write drama texts. This research used observation, interviews, documentation studies, and questionnaires as its methods. The analysis techniques used were descriptive qualitative and quantitative analysis. The results of this study are fourfold: (1) the planning for using historical films in learning to write drama texts includes the main objectives of using historical films, criteria for selecting historical films, the platforms used to select historical films, and the integration of historical films into the learning process, (2) the implementation consists of three stages: introduction, main activity, and closing, applying the discovery learning method, (3) the students’ learning outcomes using historical films in writing drama texts reached an average score of 82, categorized as good. (4) the students’ responses to the use of historical films in writing drama texts obtained an average score of 35.78, categorized as positive.